2022
DOI: 10.21203/rs.3.rs-2131671/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Principles for the effective implementation of value-based healthcare: a scoping review and proposed process model for successful implementation

Abstract: Background Porter's value-based healthcare (VBHC) idea has gained immense popularity in literature and practice in the past decade. While the value agenda clearly articulates the goal and content of VBHC, it provides no advice on an implementation strategy. This is problematic as, without an appropriate implementation strategy, even the most significant improvement initiatives are bound to fail. In this research, we adopt a change management perspective to understand better the critical principles that determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Globally, the adoption of value-based health care for the oral health context has been limited but shows promise and could support progress to achieve universal health coverage that includes oral health ( Nguyen et al ., 2023a ). Successful implementation of value-based health care requires strong leadership, significant organizational commitment and effort and priority alignment ( Renting et al ., 2022 ). From a population oral health perspective, effective health promotion is pivotal but remains absent from the value-based health care literature.…”
Section: Enabling Population Oral Health Reform Through Leadershipmentioning
confidence: 99%
“…Globally, the adoption of value-based health care for the oral health context has been limited but shows promise and could support progress to achieve universal health coverage that includes oral health ( Nguyen et al ., 2023a ). Successful implementation of value-based health care requires strong leadership, significant organizational commitment and effort and priority alignment ( Renting et al ., 2022 ). From a population oral health perspective, effective health promotion is pivotal but remains absent from the value-based health care literature.…”
Section: Enabling Population Oral Health Reform Through Leadershipmentioning
confidence: 99%
“…Our study in Chapter 3 of this dissertation also acknowledged the limitations in the models of outcome measurement in other countries (Renting et al, 2022;Heijsters et al, 2022;Cossio-Gil et al, 2022;Noel, 2022;van Staalduinen et al, Varela-Rodríguez et al, 2022;Arora et al, 2016). For instance, the authors of an outcome measurement model that was implemented and piloted in a tertiary hospital in Spain reported that the implementation phase might last 18-24 months per medical condition with a cost of 90,000-250,000 Euros (Varela-Rodríguez et al, 2022).…”
Section: Implications For Research and Policymentioning
confidence: 71%
“…For instance, health outcomes for heart failure patients would differ from those for cancer or diabetic patients. Therefore, improving value necessitates thorough planning and management to ensure the accurate measurement of the effectiveness of the healthcare services in achieving the desired health outcomes aligned with the goals in the healthcare setting (Renting et al, 2022).…”
Section: List Of Tables and Figuresmentioning
confidence: 99%
See 2 more Smart Citations